PENGARUH PENAMBAHAN NIKEL TERHADAP STRUKTUR MIKRO DAN SIFAT MEKANIS PADA BAJA BAINITIK NIR KARBIDA UNTUK APLIKASI BAJA TAHAN PELURU - , GABRIELLY H.D NABABAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Armour steel is steel that widely used as a material for armoured cars. The requirements for armour steel are must have high strength, hardness, toughness and have good ballistic performance. The aim of this research is to study about the effects of nickel addition to microstructure, mechanical and ballistic properties of CFB steels (carbide-free bainitic steels) for armour steel application. Three CFB steels with compositions of C (0,3%), Si (0,75-1%), Cr (1,7-2,3%), Mn (2-2,21%), Mo (0,25%), Cu (0,28-0,48%) and Ni (0,3-2,4%) were made by casting. Three CFB steel alloys are categorized by levels of nickel contained in the alloy, the alloy 1 (0,33% Ni), alloys 2 (1,23% Ni) and alloys 3 (2,44% Ni). Steels were tested based on the levels of nickel contained in the alloy to determine whether differences in the levels of nickel effect on microstructure and mechanical properties or not. Tests carried out include tensile, impact, hardness, microstructure, ballistic test and weldability. The results showed that the differences in the levels of nickel had little influence on the microstructure of each alloy, but affects the mechanical properties of CFB steel alloys. Tensile and impact test results show that the CFB steel does not qualify to be used as armour steels, while the hardness test results meet the requirements as armour steels. Ballistic test showed that the CFB steels are bullet-proof. The weldability test showed that CFB steel has good weldability properties. The test results indicate that the higher levels of nickel contained in CFB steel alloy can improve the mechanical properties of CFB steel.